Peer-to-peer learning on vegetable production and implications for value chain development in Nigeria - Aju, Stellamaris; ter Steeg, Emily; van den Berg, Marrit (International Food Policy Research Institute, 2024)
The vegetable sector of Kaduna and Kano states in Nigeria is crucial for smallholder farmers' livelihoods, providing employment opportunities and contributing to good health. However, unfavorable environmental conditions and poor agronomic practices have hindered its development, leaving farming households struggling with food insecurity, nutrient deficiency, and poverty. Furthermore, societal expectations regarding gender roles, religious beliefs, and cultural practices make it more challenging for couples to work together effectively and attain the best possible outcomes for their family. The East-West Seed Knowledge Transfer (EWS-KT) foundation is supporting SHFs' access to vegetable markets through a one-year training program (across two cropping cycles) and together with Wageningen University and Research (WUR) intends to provide a gender-responsive agricultural extension system. Overall, this research project aims to improve farmers’ vegetable production, reduce the gender gap in agricultural participation and intrahousehold decision-making, and improve smallholder’s livelihoods. This report is based on a household survey covering 2562 respondents from 150 SHF communities in Kaduna and Kano. The baseline survey was a joint effort of Datametrics Associates Ltd. and WUR, consisting of two data collection rounds: the main survey round and supplementary survey round. Together, the surveys cover the different groups part of the study: key farmers, core farmers, other peer farmers, and the spouses of these farmers. The baseline survey provides insight into current agronomic practices, agricultural extension activities, SHF livelihoods, and women empowerment in Kaduna and Kano. Moreover, it assessed to which extent characteristics are balanced across socio-economic characteristics and current outcome indicators irrespective of their assignment to the treatment and control groups. Findings also helped to improve the formulated indicators for the evaluation of the project interventions.